NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL CAHAYA DI PENJURU HATI KARYA ALBERTHIENE ENDAH - Nanda - Saputra (sarasvati, 2021)
Abstract Moral education is a core component in the world of education. Because humans need not only knowledge but also religious spiritual strength to form a complete human being (insan kamil) in accordance with Islamic norms. One of the ways is through high-quality literary works, namely the novel Light in the corner of the Heart by Alberthiene Endah. This study aims to determine: 1) The values of moral education in relation to God. 2) The values of moral education in relation to oneself. 3) The values of moral education in relation to others. This research is a descriptive qualitative type of research, while the data used is in the form of verbal data in the form of dialogue between characters, narratives, signs that describe moral education, and quotes that describe moral education. The data analysis used in this research is content analysis. The results of this study include three things. 1) There are three values of moral education in relation to God, namely: faith in God, obedience to worship and gratitude. 2) There are ten moral values in relation to oneself, namely: honesty, responsibility, healthy lifestyle, discipline, hard work, confidence, entrepreneurial spirit, creative, independent and curiosity. 3) There are three moral values in relation to others, namely: being aware of one's obligations and of others, appreciating achievements and being friendly.Keywords: values, moral education, novels